Forests and climate change in Latin America: linking adaptation and mitigation - Locatelli, Bruno; Evans, V.; Wardell, A.; Andrade, A.; Vignola, Raffaele (2011)
Climate change can be addressed by mitigation (reducing the sources or enhancing the sinks of greenhouse gases) and adaptation (reducing the impacts of climate change). Mitigation and adaptation present two fundamentally dissimilar approaches whose differences are now well documented. Forest ecosystems play an important role in both adaptation and mitigation and there is a need to explore the linkages between these two options in order to understand their trade-offs and synergies. In forests, potential trade-offs can be observed between global ecosystem services, such as the carbon sequestration relevant for mitigation, and the local ecosystem services that are relevant for adaptation. In addition, mitigation projects can facilitate or hinder the adaptation of local people to climate change, whereas adaptation projects can affect ecosystems and their potential to sequester carbon. Linkages between adaptation and mitigation can also be observed in policies, but few climate change or forest policies have addressed these linkages in the forestry sector. This paper presents examples of linkages between adaptation and mitigation in Latin American forests. Through case studies, we investigate the approaches and reasons for integrating adaptation into mitigation projects or mitigation into adaptation projects. We also analyze the opportunities for mainstreaming adaptation–mitigation linkages into forest or climate change policies